Lymphocyte reactivity to mitogens in subjects with systemic lupus erythematosus, rheumatoid arthritis and scleroderma. - Horwitz, D A (1977)
The mitogenic reactivity of lymphocytes from subjects with systemic lupus erythematosus, rheumatoid arthritis and scleroderma was studied. Cultures containing either unseparated or separated lymphocytes were stimulated with phytohaemagglutinin, Con A and pokeweed mitogen after inhibitory serum factors were eluted from the cell surface. Incorporation of [3H]thymidine in patient cultures was compared to that of normal controls. Greatly decreased reactivity was found in SLE to all three mitogens. Significantly decreased values to some mitogens was also observed in rheumatoid arthritis and scleroderma, but the defect was less severe. Cultures of study subjects contained significantly fewer small lymphocytes than normal controls and this finding explained at least in part the decreased mitogenic reactivity.